Energy Diplomacy During Crisis: A Case Study of India’s Foreign Policy Adjustment Strategies in Facing the Potential Global Oil Shock in 2019 - Rudiany, Novita Putri; Permana, Adinda Reisha Elmaharani; Montratama, Ian (Global Strategis, 2025)
This article aims to elaborate on how a state adjusts its energy diplomacy in the event of a potential global energy crisis, using India’s foreign policy adjustment following the drone attack on the global oil supplier as a case study. The 2019 drone attack incident that occurred at Saudi Arabia’s Aramco oil refinery hampered Saudi Arabia’s oil supply in exporting petroleum and caused global oil prices to increase by around five percent. This event raised concerns for India, which depends on Saudi Arabian oil imports. India’s dependence on petroleum continues to grow annually due to its large population and rapid industrial development. This research examines the Indian government’s strategy for securing its oil supply in response to the imbalance in Saudi Arabian oil production. The method used in this research is qualitative, emphasizing comprehensive and descriptive analysis regarding India’s energy security. Additionally, this research was analyzed using policy adjustment strategies, which emphasize a defensive approach, as evident in the Indian government’s cautious response and actions. The results of this research reveal two distinct defensive strategies, both domestic and international. On the one hand, India utilizes its domestic strategic petroleum reserves, and on the other hand, India has decided to strengthen its collaboration with Russia and Venezuela. The analysis is also connected to energy security to identify India’s energy diplomacy strategy during a crisis. Keywords: Energy Diplomacy, India, Saudi Arabia, Policy Adjustment, Energy Security, Global Oil Crisis Artikel ini bertujuan untuk menguraikan bagaimana suatu negara menyesuaikan diplomasi energinya ketika ada kemungkinan terjadinya krisis energi global, dengan studi kasus penyesuaian kebijakan luar negeri India setelah serangan drone terhadap pemasok minyak global. Insiden serangan drone pada tahun 2019 yang terjadi di kilang minyak Saudi Aramco, Arab Saudi, berpotensi menghambat pasokan minyak Arab Saudi dalam mengekspor minyak bumi dan menyebabkan harga minyak global meningkat sekitar lima persen. Peristiwa ini menimbulkan kekhawatiran bagi India yang bergantung pada impor minyak Arab Saudi. Ketergantungan India terhadap minyak bumi terus meningkat setiap tahunnya karena jumlah penduduk yang signifikan dan peningkatan pembangunan industri. Penelitian ini menganalisis strategi pemerintah India dalam mengamankan pasokan minyaknya sehubungan dengan ketidakseimbangan minyak Arab Saudi. Metode yang digunakan dalam penelitian ini adalah kualitatif, menekankan analisis komprehensif dan deskriptif mengenai keamanan energi India. Selain itu, penelitian ini dianalisis dengan menggunakan strategi penyesuaian kebijakan yang menekankan pada strategi defensif, terlihat dari respons dan tindakan pemerintah India yang berhati-hati. Hasil penelitian ini menunjukkan dua strategi pertahanan domestik dan internasional. Di satu sisi, India menggunakan cadangan minyak strategis dalam negerinya dan di sisi lain, India memutuskan untuk memperkuat kolaborasinya dengan Rusia dan Venezuela. Analisis ini juga dikaitkan dengan ketahanan energi agar dapat menemukan strategi diplomasi energi India di tengah situasi krisis. Kata-Kata Kunci: Diplomasi Energi, India, Arab Saudi, Penyesuaian Kebijakan, Keamanan Energi, Krisis Minyak Global